2020
DOI: 10.1371/journal.pone.0231986
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unsuccessful treatment outcomes and mortality among tuberculosis patients in Malaysia: A registry-based cohort study

Abstract: smoking, extrapulmonary TB, history of previous TB treatment, advanced chest radiography findings and human immunodeficiency virus (HIV) infection. Factors found associated with all-cause mortality were similar except for nationality (higher among Malaysians) and place of residence (higher among rural dwellers), while smoking and history of previous TB treatment were not found to be associated with all-cause mortality. Conclusions This study identified various sociodemographic characteristics and TB disease-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 23 publications
(38 reference statements)
4
38
6
Order By: Relevance
“…This means that, despite the high uptake of HIV testing in TB patients in Armenia, there is a probability of missed opportunities to link HIV co-infected cases to the appropriate care. In our study, about 80% of cases with "not tested" status of HIV and unsuccessful treatment outcome were LTFU, which is consistent with the existing literature [12,33]. One explanation would be that the patient's refusal for HIV test may influence the provider's interaction with the patient, which may cause the patient to feel pressure and interrupt the treatment or leave the program and non-consent for HIV test might be an indicator of overall poor adherence to TB treatment [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This means that, despite the high uptake of HIV testing in TB patients in Armenia, there is a probability of missed opportunities to link HIV co-infected cases to the appropriate care. In our study, about 80% of cases with "not tested" status of HIV and unsuccessful treatment outcome were LTFU, which is consistent with the existing literature [12,33]. One explanation would be that the patient's refusal for HIV test may influence the provider's interaction with the patient, which may cause the patient to feel pressure and interrupt the treatment or leave the program and non-consent for HIV test might be an indicator of overall poor adherence to TB treatment [11].…”
Section: Discussionsupporting
confidence: 92%
“…This study also has several limitations. We did not have data on TB patients' nationality and residency, which are a known factors influencing the TB treatment outcome [33,34]. Previous studies in Armenia indicated about 95% of the registered TB patients in Armenia are natives, holding Armenian citizenship [32], which means that effect of this variable in our adjusted estimates would be minimal.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies conducted in Ethiopia and Pakistan excluded chest X-ray results due to the availability of variables in their NTP database [ 9 , 12 , 14 ]. Recent local studies found an association of chest X-ray findings with unfavourable outcomes; however, these studies were conducted among all age groups [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, it has been proven that sociodemographic factors such as age [ 4 ], gender [ 5 ], race [ 6 ], educational level [ 7 ], employment [ 8 ], health care worker [ 9 ], income [ 10 ], residency [ 11 ], nationality [ 12 ], country of origin [ 13 ], and smoking status [ 14 ] have a role in TB cases. However, evidence described in the literature confirmed the importance of conducting a study to better understand how air quality and weather can influence the cases of TB.…”
Section: Introductionmentioning
confidence: 99%